Tourism development strategies for business tourism destinations: Case study in the central region of Portugal - Marques, Jorge (2017)
The purpose of this paper is to present the results of a Delphi study about the strategic importance of business tourism in the Central Region of Portugal (territory encompassing the cities of Coimbra, Aveiro and Viseu), where the presence of a qualified and diverse tourism offer combined with the existence of varied venues and quality accommodation can contribute to provide a valued tourism experience associated with the meetings Industry. This study allows a reflection on the potential of business tourism in territories where this sector is not always given due attention by local, regional and national tourism bodies. These smaller urban centres (compared with the main urban centres of Lisbon and Oporto), relatively close to each other, may find strategic advantages in joint action, considering that these three geographic areas complement each other in the integrated supply of tourism products, experiences, support services and facilities. Primary data was collected through a Delphi study with the aim of identifying regional tourism stakeholders' perceptions of the importance and potential of business tourism development and strategies that should be put in place to this end. The results show that stakeholders identify business tourism as a strategic product that should be developed, and indicate some development strategies to be considered in this territory.